EAST KALIMANTAN PROVINCE'S PARADIPLOMACY IN HANDLING SUSTAINABLE TOURISM DEVELOPMENT OF DERAWAN ISLAND - Wahyu Dwi Pambagyo; Sidik Jatmika (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2025)
Paradiplomacy, the international activities of sub-national governments, has become increasingly relevant in environmental governance and sustainable tourism, particularly within decentralized political systems. Indonesia's regional autonomy has enabled provinces such as East Kalimantan to build cross-border partnerships, environmental cooperation frameworks, and tourism promotion networks that transcend national diplomatic channels. Derawan Island, one of Indonesia's most renowned marine tourism destinations, is facing increasing pressures from mass tourism, coral degradation, inadequate waste management, and socio-economic transformation. This article examines how East Kalimantan Province employs paradiplomacy as a strategy to promote sustainable tourism development on Derawan Island. Drawing on a qualitative analysis of regional policies, provincial cooperation initiatives, institutional arrangements, and global environmental partnerships, this paper argues that paradiplomacy has emerged as a tool for capacity building, green tourism innovation, and adaptive environmental governance. Yet, structural challenges, including fragmented authorities, limited local capacity, asymmetrical relations with foreign partners, and weak ecological enforcement, continue to undermine progress. This research contributes to the discourse on subnational diplomacy in maritime Southeast Asia and provides recommendations for enhancing East Kalimantan's international engagement to support sustainable island tourism.